HUMANISTIC AND SPIRITUAL DIMENSIONS OF WOMEN’S EXPERIENCE IN CHILDBIRTH IN QS. AL-AḤQĀF/46: 15 AND QS. MARYAM/19: 22–26 - Nabilah Nuraini; Syauqi Aulade Ghifari (Takafu: Journal of Tafsir and Gender Perspective, 2025)
This article examines the lived experience of women in childbirth as portrayed in two Qur’anic passages—QS. al-Aḥqāf [46]:15 and QS. Maryam [19]:22–26—through a qualitative descriptive–analytical framework. Integrating textual, contextual, and hermeneutical approaches, the study investigates how the Qur’an articulates both the human dimension (al-insāniyyah) and the spiritual dimension (al-rūḥāniyyah) of the maternal experience. Surah al-Aḥqāf underscores an ethical-normative vision, portraying the mother’s suffering and sacrifice as the moral foundation of birr al-wālidayn (filial devotion). Conversely, Surah Maryam presents an existential-spiritual encounter in which Maryam’s solitude, anguish, and submission (tawakkul) reflect the depth of human faith in the face of divine will. Drawing upon the works of classical exegetes such as al-Ṭabarī, al-Qurṭubī, and Ibn Kathīr, alongside contemporary interpretations by M. Quraish Shihab, this study argues that the Qur’an transcends the biological description of childbirth and reveals its theological and existential depth. Childbirth emerges not merely as a physiological process but as a sacred intersection between the human and the Divine, where pain becomes a vessel of raḥmah (divine mercy) and maternal love embodies the compassionate presence of God within creation.